A Multimodal Analgesic Protocol with Gabapentin-dexmedetomidine for Post-operative Pain Management after Modified Radical Mastectomy Surgery: A Randomized Placebo-Controlled Study - Abdallah, Nasr Mahmoud; Bakeer, Ahmed Hussain (Open Access Macedonian Journal of Medical Sciences, 2022)
Background and Aim: Modified radical mastectomy (MRM) is accompanied by severe acute postoperative pain. This study evaluated the safety and efficacy of oral gabapentin plus dexmedetomidine infusion as an analgesic multimodal protocol in patients undergoing MRM. Methods: This prospective randomized, double-blind placebo-controlled study included 30 females scheduled for MRM from June 2021 to December 2021. They were randomly divided into two groups. GD Group (n=15) received oral gabapentin 400 mg and IV infusion of Dexmedetomidine 0.4 µg/kg/h over 10 min after a bolus of 0.5 µg/kg before induction of general anesthesia. Placebo Group (n=15) received a placebo capsule and saline infusion identical to the GD Group. The primary outcome measure was total morphine consumption, and secondary outcomes were pain and sedation scores and intraoperative fentanyl consumption. Results: Pain score was significantly lower in the GD Group than the Placebo group, starting immediately postoperative up to 24 hours except after 18 hours. The total intraoperative fentanyl consumption and postoperative morphine consumption were significantly lower in the GD Group. The sedation score was significantly higher in the GD Group compared to the Placebo group immediately postoperative and after 2 hours. The heart rate and mean arterial pressure were within the clinically accepted ranges intra- and postoperatively in the two groups. Conclusion: Preemptive oral gabapentin plus dexmedetomidine IV infusion is a safe and effective analgesic alternative for patients undergoing MRM.